2022
DOI: 10.1021/jacs.1c12636
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic CO2 Reduction Using Water as an Electron Donor under Visible Light Irradiation by Z-Scheme and Photoelectrochemical Systems over (CuGa)0.5ZnS2 in the Presence of Basic Additives

Abstract: We demonstrated photocatalytic CO2 reduction using water as an electron donor under visible light irradiation by a Z-scheme photocatalyst and a photoelectrochemical cell using bare (CuGa)0.5ZnS2 prepared by a flux method as a CO2-reducing photocatalyst. The Z-scheme system employing the bare (CuGa)0.5ZnS2 photocatalyst and RGO-(CoO x /BiVO4) as an O2-evolving photocatalyst produced CO of a CO2 reduction product accompanied by H2 and O2 in a simple suspension system without any additives under visible light irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…39 When the fine particulate (CuGa) 0.5 ZnS 2 is applied to a Zscheme system, photocatalytic water splitting and CO 2 reduction are much enhanced (Figure 4B). 4 The Z-scheme CO 2 reduction activity strongly depends on the reactant solution conditions (Table 4, entries 5−8). Addition of a basic salt not only stabilizes but also enhances Z-scheme CO 2 reduction because of efficient supply of hydrated CO 2 to the photocatalyst surface.…”
Section: Visible-light Responsive Metal Sulfide Photocatalysts For Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…39 When the fine particulate (CuGa) 0.5 ZnS 2 is applied to a Zscheme system, photocatalytic water splitting and CO 2 reduction are much enhanced (Figure 4B). 4 The Z-scheme CO 2 reduction activity strongly depends on the reactant solution conditions (Table 4, entries 5−8). Addition of a basic salt not only stabilizes but also enhances Z-scheme CO 2 reduction because of efficient supply of hydrated CO 2 to the photocatalyst surface.…”
Section: Visible-light Responsive Metal Sulfide Photocatalysts For Co...mentioning
confidence: 99%
“…The bare (CuGa) 0.5 ZnS 2 photocathode reduces CO 2 to CO with high stability under visible light with application of an external bias (Figure 5B). 4 Faradaic efficiencies for CO and H 2 formation are 20% and 80%, respectively, being almost 100% of total Faradaic efficiency. It is stressed that high CO formation is observed even without cocatalyst and surface modification on the photocathode.…”
Section: Visible-light Responsive Metal Sulfide Photocatalysts For Co...mentioning
confidence: 99%
“…(b) and (c) Reproduced with permission. 57 Copyright 2022, American Chemical Society. apparent quantum yields of 59.1% and 5.6%, respectively, at 340 nm and 420 nm for CO 2 reduction to HCOOH (Fig.…”
Section: Active Site Construction For Co 2 Photoreductionmentioning
confidence: 99%
“…10b and c). 57 Thus, band engineering is a useful strategy for both HER and CO 2 RR photocatalyst design. It can also be found that (CuGa) 0.5 ZnS 2 shows better performance than CuGaS 2 in reducing CO 2 to CO under the same reaction conditions (Fig.…”
Section: Design Of Efficient Zns-based Photocatalytic Systemsmentioning
confidence: 99%
See 1 more Smart Citation